The Metabolomic Signature of Opa1 Deficiency in Rat Primary Cortical Neurons Shows Aspartate/Glutamate Depletion and Phospholipids Remodeling - Chao de la Barca, Juan Manuel (Sci Rep, 2019)
Pathogenic variants of OPA1, which encodes a dynamin GTPase involved in mitochondrial fusion, are responsible for a spectrum of neurological disorders sharing optic nerve atrophy and visual impairment. To gain insight on OPA1 neuronal specificity, we performed targeted metabolomics on rat cortical neurons with OPA1 expression inhibited by RNA interference. Of the 103 metabolites accurately measured, univariate analysis including the Benjamini-Hochberg correction revealed 6 significantly different metabolites in OPA1 down-regulated neurons, with aspartate being the most significant (p < 0.001). Supervised multivariate analysis by OPLS-DA yielded a model with good predictive capability (Q(2)(cum) = 0.65) and a low risk of over-fitting (permQ2 = −0.16, CV-ANOVA p-value 0.036). Amongst the 46 metabolites contributing the most to the metabolic signature were aspartate, glutamate and threonine, which all decreased in OPA1 down-regulated neurons, and lysine, 4 sphingomyelins, 4 lysophosphatidylcholines and 32 phosphatidylcholines which were increased. The phospholipid signature may reflect intracellular membrane remodeling due to loss of mitochondrial fusion and/or lipid droplet accumulation. Aspartate and glutamate deficiency, also found in the plasma of OPA1 patients, is likely the consequence of respiratory chain deficiency, whereas the glutamate decrease could contribute to the synaptic dysfunction that we previously identified in this model.